Artificial intelligence in project management: Systematic literature review - Bento, S.; Pereira, L.; Gonçalves, R.; Dias, Á.; Lopes da Costa, R. (International Journal of Technology Intelligence and Planning, 2022)
Project management is a common field in many industries, and it is not immune to the innovations that artificial intelligence is bringing to the world. Even so, the application of artificial intelligence is not that widespread in companies and especially not in all of project management areas. The reasons are not clear but seem to be related to the uncertainty of the application of artificial intelligence in project management. The purpose of this paper was to acknowledge the potentialities and limitations of artificial intelligence in the specific area of project management by doing a systematic literature review with which it was possible to analyse and correlate the selected articles and reach some patterns and tendencies. In the end, it was clear that there is an increased interest in the scientific community in this field, although with some areas to explore.